STUDENTSâ PERSONALITY IN ENGLISH LANGUAGE TEACHING - Ismih, Fajarsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2013)
Happiest teaching....the biggest problem will be the nicest thing whenit can Â be overcome. English Language Teaching in Indonesia seems still to be problematic, in term of curriculum, teacher and student. Regarding the students, possessing well self-esteem and willingness to take a risk in learning English are the two major aspects of personality factors from the affective domain that contribute much in the success of English Language Teaching.There are three agents influence in building the learnersâ self-esteem and risk-taking; parent/family, teacher and school. It is actually a must for the parents to provide more space and time for their children to have a chance to show and develop their capability, thus they can have a high confidence. Teacher on the other side should try to always encourage the students to perform their English by creating and maintaining the learnerâs involvement in every English activity.Making a deal of the teaching and learning activities in the very beginning of the meeting, creating both the rule and the fine during the period of study, making a class commitment to reach the goal of learning English, encouraging to perform just what they way they are, creating the fun and friendly environment and giving any compliment of any small progress are the possible solution to tackle the problems on studentsâ confidence and risk-taking.Providing a special space, teacher and program just for a student with very critical problem on their personality is another proposed solution to the school.